Dictamnine is an effective anti‐anaphylactoid compound acting via the MrgX2 receptor located on mast cells. (24th April 2021) - Liu, Rui; Hu, Shiling; Ding, Yuanyuan; Wang, Jue; Wang, Yuejin; Gao, Jiapan; He, Langchong
Abstract : Anaphylactoid reactions are potentially fatal allergic diseases caused by mast cells (MCs), which release histamine and lipid mediators under certain stimuli. Therefore, there is an urgent need to develop new drug candidates to treat anaphylactoid reactions. The MrgX2 receptor mediates anaphylactoid reactions that cause inflammatory diseases. Cortex dictamni is a Chinese herb used for treating allergy‐related diseases; however, its active compound is still unknown and its mechanism of action has not yet been reported. The aim of this study was to screen the anti‐anaphylactoid compound from C . dictamni extracts. An MrgX2/CMC‐HPLC method was established for screening MrgX2‐specific compounds retained from the alcohol extract of C . dictamni . A mouse model of hindpaw extravasation was used to evaluate the anti‐anaphylactoid effect of this ingredient. Intracellular Ca 2+ mobilization was assessed using a calcium imaging assay. Enzyme immunoassays were performed to measure cytokine and chemokine release levels. The molecular signaling pathways were explored by western blotting. As a result, dictamnine was identified as an effective compound using the MrgX2/CMC method, which remarkably suppressed MC intracellular Ca 2+ mobilization and the release of de novo degranulated substances, and inhibited PKC‐PLCγ‐IP3R‐associated protein signaling molecules. Hence, dictamnine is a novel therapeutic candidate for anaphylactoid reactions via MrgX2.